Transforming Pesantren Management: The Role of Women’s Leadership in Indonesia - Taqiyuddin Taqiyuddin; Nurmalasari Nurmalasari; Hanifah Amalia Zahra (MASI Mandiri Edukasi, 2026)
The leadership structure of Islamic boarding schools (pesantren) in The leadership structure of Islamic boarding schools (pesantren) in Indonesia has traditionally been dominated by male religious authorities, leaving the role of women in institutional leadership relatively underexplored in academic discourse. Although previous studies have discussed gender issues in Islamic education, limited attention has been given to how female leaders shape managerial practices and institutional development within pesantren. This study addresses this gap by examining the characteristics, strategies, and institutional impacts of female leadership in pesantren management. This research employs a qualitative design based on a systematic literature review combined with case-based analysis of selected pesantren led by women. Data were collected from peer-reviewed journal articles, books, and institutional reports, and analysed using thematic analysis, including coding, categorisation, and interpretation of leadership patterns, decision-making processes, and management practices. The findings reveal that female leadership in pesantren is characterised by collaborative decision-making, participatory governance, and strong community engagement. Women leaders tend to adopt adaptive management strategies by integrating traditional Islamic values with contemporary educational practices. These approaches contribute to improving institutional governance, enhancing educational quality, and strengthening the sustainability of pesantren in responding to social and educational changes. This study contributes to the literature by providing a more nuanced understanding of how female leadership influences organisational transformation in Islamic educational institutions. It also offers a conceptual perspective on gender-inclusive leadership as a strategic factor in promoting innovation and sustainability in pesantren management while maintaining their religious identity.